Diversity of Bivalves in Cengkrong Mangrove Trenggalek, East Java Based on Morphological and Molecular Character - Mukhlis, Mukhlis; Niken Satuti Nur Handayani; Trijoko (Masyarakat Moluska Indonesia, 2024)
Bivalves in mangrove ecosystem plays an important role in the process of litter decomposition and mineralization of organic matter, especially that are herbivores and detrivor. Bivalves in one ecosystem can be known by looking the morphologic character, while the molecular character can be use to know the genetic variation of species in population. The purpose of this research was to determine species diversity of bivalve, and to understand the morphological and molecular characters of them. Phenetic Similarity analyzed using 109 morphological characters, ISSR 6 ISSR 8 primer. The results were analyzed using MVSP 3.1 (Multi-Variate Statistical Package) program to obtain a dendogram that show similarity of bivalves. Four species of bivalves identified, consisting of Polymesoda Erosa, Meretrix meretrix, Pholas sp., and Glauconome virens. Based on morphological and molecular analysis showed two main clusters with the similarity of 54.8% for morphology and 57.6% for molecular. Based on analysis of morphological and molecular characters, it can be concluded that the diversity of the bivalves in ​​mangrove forests Cengkrong is influenced by morphological structure, meristik, morphometric shell, and the type of habitat.